2022
DOI: 10.1177/1351010x221104892
|View full text |Cite
|
Sign up to set email alerts
|

Classroom acoustics and cognition: A review of the effects of noise and reverberation on primary school children’s attention and memory

Abstract: Classroom acoustic conditions are often suboptimal, so how do they affect children’s cognition? This review synthesized research assessing the effect of different classroom acoustic conditions on children’s attention and memory. A comprehensive search of four online databases was conducted in January 2022 using the search term classroom AND (noise* OR reverberat* OR acoustic*) AND (cognit* OR attention OR memory OR processing). The results revealed 21 relevant papers plus an additional 10 from their references… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Only one study examined the effect of external noise and this was road traffic noise [42]. It may be beneficial to study other types of noise such as aircraft or rail noise which can be heard in classrooms and have been shown to have negative effects on other processes such as reading and cognition (see [2] and [5] for reviews). Though it is important to note from this review that speech distractors had a greater negative affect than classroom noise without speech [40] and unintelligible classroom noise had a greater negative affect than road traffic noise [42].…”
Section: Noise Typementioning
confidence: 99%
See 2 more Smart Citations
“…Only one study examined the effect of external noise and this was road traffic noise [42]. It may be beneficial to study other types of noise such as aircraft or rail noise which can be heard in classrooms and have been shown to have negative effects on other processes such as reading and cognition (see [2] and [5] for reviews). Though it is important to note from this review that speech distractors had a greater negative affect than classroom noise without speech [40] and unintelligible classroom noise had a greater negative affect than road traffic noise [42].…”
Section: Noise Typementioning
confidence: 99%
“…If the presentation is in the auditory domain, then it is important to note that speech intelligibility and processing speed can be negatively affected [57,58]. If the presentation is in the visual domain, noise can have a negative effect on children's visual short-term memory, reading, and writing performance (see [4,5], and [2] for reviews). In terms of outcome measures to assess, including both accuracy of solving the mathematical problem and speed of response is useful as included in several of the studies reviewed [33,[36][37][38].…”
Section: Assessment Typementioning
confidence: 99%
See 1 more Smart Citation
“…These effects can be either from acute exposure, or chronic exposure over a long period of time. Poor classroom acoustic conditions can negatively affect children’s speech perception, 3,4,12,15 comprehension (see Lamotte et al 16 and Schiller 17 for reviews), literacy outcomes (see Mealings 18 for a review), cognition (see Mealings 19 for a review), and physical health (see Mealings 20 for a review). These negative effects on the learning processes can affect children’s academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…1 Reviews have shown that poor classroom acoustic conditions can affect children's speech perception, comprehension, literacy, numeracy, cognition, learning and even physical health and mental well-being. [2][3][4][5][6][7][8][9][10] But what effect do different classroom acoustic conditions have on different children's behaviour?…”
Section: Introductionmentioning
confidence: 99%